TI_GERICHTE 36.2017.38 vom 26. Juni 2017 , Pagamento premi: premio indicato dall'assicuratore con importi diversi - TI Tribunale d'appello (2017)
Pagamento premi: premio indicato dall'assicuratore con importi diversi